Tuning of the parameters of damping controllers for power electrical systems using Bioinspired Algorithms - Miotto, Ednei L.; Araujo, Percival B. De [UNESP]; Andre Takahashi, L. M. [UNESP]; Fortes, Elenilson De V. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This work present a new current injection model (CSM) to represent the FACTS device Generalize Unified Power Flow Controller (GUPFC) in power flow programs. The goal is to validate the proposed model to the controlled of active and reactive power flows in a test system known in the literature as Two-Area Symmetrical system. This work will also analyze the performance of the Novel Bat Algorithm in the coordinated tuning of the parameters of supplementary damping controllers. The goal is to introduce minimal damping rates to low frequency electromechanical oscillation modes as specified by the design. The performance of the Novel Bat Algorithm in the coordinated tuning of controllers was compared with Classic Bat Algorithm. The results of simulations performed showed that the FACTS GUPFC device proposed in this work acted correctly in the control of power flows and in the improvement of the voltage profile for the analyzed test system. In addition, it was concluded that the Novel Bat Algorithm as a promising tool for the analysis of small-signal stability.
Keywords: CSM; Novel Bat Algorithm; Power oscillation damping; Power system stabilizers; Small-signal stability